Relationship between service quality and customer satisfaction during halal certificate application in Kelantan / Mariam Setapa...[et al.] - Setapa, Mariam; Kamarul Zaman, Liziana; Wan Mustapha, Wan Asma Hanim; Mohd Kanafiah, Siti Farah Haryatie; Mohd Noor, Nor Raihana Asmar (Universiti Teknologi Mara Cawangan Kelantan, 2020)
In Malaysia, only JAKIM and JAIN are given full authority to grant and certify halal certification. Certain criteria have been set in order for business or individuals to be awarded a halal certification. Even though the process of applying for a halal certificate may take some time, it can be executed promptly if the applicant's documentation is ready beforehand as in it complies with the requirements provided. Nevertheless, some parties contended that strict governance in the process of obtaining the halal certificates preventing the smoothness of certification process. Thus, this paper intends to study customer satisfaction during halal certificate application and the respondents came from various backgrounds of business. The independent variables are assurance, empathy, communication and security taken from SERQUAL model, meanwhile the dependent variable is customer satisfaction. The population of this study was 100 respondents who have attended a course organised by JHEAIK, but only 77 (77%) respondents were returned the questionnaire. The data was analysed using SmartPLS 3.2.1 software. The analysis shows that only empathy determined the customer satisfaction during halal certificate application meanwhile the other three variables were not the factors in determining the satisfaction among customers. Thus, the hypothesis 2 was accepted and the rest were rejected.